Urban land use spectral using high resolution imagery and GIS approach in sustaining urban planning spatial databases - Mohd. Noor, Norzailawati; Abdullah, Alias; Myint, Khin Cho (2013)
Remote sensing technology is useful for urban planning due to its capability in examining detailed spectral characteristic of urban land uses. This study attempts to review a relevant studied have been done in identified an appropriate spectral for urban land use using high resolution remote sensing images and GIS approach. The detailed spectral for urban land uses consist of residential, industrial and commercial in metropolitan and city center urban hierarchy will be discussed. The segmentation techniques through object oriented and the use of field measurement was highlighted, at once demonstrates the usability of such infrastructure to facilitate further progress of remote sensing and GIS application in urban planning in Malaysia. Finally, a discussion of the needs for further research is presented.